Influence of divalent metal ions on gelation of a short heterochiral peptide - Pota, Giulio; Florio, Daniele; Cimmino, Luca; Netti, Paolo Antonio; Panzetta, Valeria; Marasco, Daniela; La Manna, Sara (Frontiers in Drug Discovery, 2025)
Peptide self-assembly has emerged as a powerful and versatile strategy for the design of supramolecular biomaterials with tunable structural and functional properties. Through the precise organization of short peptide sequences, it is possible to construct nanostructured materials that mimic biological architecture and respond to specific environmental cues. Among the various design elements that influence peptide assembly, the incorporation of metal ions has gained increasing attention as a means to modulate material properties and endow biofunctionality. In this study, we investigated the distinct effects of four divalent metal cations—calcium (Ca2+), magnesium (Mg2+), zinc (Zn2+), and copper (Cu2+)—on the hydrogel-forming capabilities of Ac-(L-Phe)-(L-Ile)-(L-Asn)-(D-Tyr)-(L-Val)-(L-Lys)-CONH2 (FINyVK), an ultrashort heterochiral hexapeptide derived from the second helix of the C-terminal domain of Nucleophosmin 1 (NPM1), a nucleolar protein implicated in both structural maintenance and disease-related aggregation. This peptide sequence is amyloidogenic and capable of forming hydrogels under appropriate conditions. By employing a comprehensive set of biophysical techniques, including circular dichroism (CD), rheology, electron microscopy, and thermal analysis, we characterized the conformational and morphological properties of hydrogels formed both in the presence and absence of metal ions. Our findings revealed that metal coordination can significantly alter peptide assembly pathways, influencing key features such as fibrillar thickness, network porosity, and the kinetics of gelation. Notably, different cations impart distinct effects: while alkaline earth metals like Ca2+ and Mg2+ enhance fibrillar alignment and promote reversible gelation, transition metals such as Zn2+ and Cu2+ tend to disrupt ordered structures due to stronger coordination with aromatic residues. These results underscore the utility of metal–peptide interactions as a rational design principle for engineering advanced peptide-based hydrogels.